PENGARUH PERBANDINGAN SURFAKTAN DAN KO-SURFAKTAN TERHADAP KARAKTERISTIK DAN KESTABILAN MIKROEMULSI MINYAK ZAITUN (Olive oil) - Devi Ratnasari; Harry Noviardi; Baiq Annisa Apriyanti A.R (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
Olive oil is a compound known to have pharmacology activity, such as anticolesterol. Low solubility of olive oil lead to become low bioavailabilitas when given orally. Olive oil need to be formulations that could improve soulubility by making microemulsion. Microemulsion is an emulsion of oil in water (o/w) or water in oil (w/o) stable thermodynamically globul-size 0,1-1 μm. Type emulsion suitable for olive oil is oil in water (o/w) because it is intended for oral consumption. This research aimed to determine the comparison of the composition of the mixture of surfactants and co-surfactants in manufacture of microemulsi as well as test the stability. Microemulsion created by using tween 80 as surfactants and sorbitol as co-surfactants with a comparison of surfactants and co-surfactant (1:1, 2:1, 3:1, 4:1, 5:1). Microemulsion formed then evaluated organoleptis, types of density, size of globul, surface tension, viscosity and centrifugation. Evaluation results indicate the composition of surfactants and co-surfactants (5:1) has a size of globul (1,71 μm) and most low surface tension (40,8507 dyne/cm). Test of stability during 8 weeks at low, room, and high temperatures with parameter that was organoleptic, pH and viscosity. Stability test results shows that changes of pH and viscosity.